Strategic Process Research: Questions and Recommendations - Fredrickson, James W. (Academy of Management Review, 1983)
The characteristics of the two most frequently cited types of strategy formulation models are compared to illustrate their major differences. A number of research issues emerge. Additional research issues then are identified in a review of literature that has raised questions about the most common model. Recommendations are provided in an attempt to help investigators pursue these and other strategic process questions.